A new record of the presence of the gametophyte of the species Asparagopsis taxiformis from the red algae Rhodophyta in the Syrian coast (Latakia University Journal -Biological Sciences Series, 2022)
The distribution and abundance of Asparagopsis taxiformis of the red algae Rhodophyta on Lattakia beach were studied over a year. The presence of the studied species was recorded in the rocky sub-littoral area of the beaches of Lattakia, Jableh and Tartous in the spring, summer, autumn and winter of 2020The species was collected with cystocarps at the beginning of summer. The increase in abundance was observed in autumn and its presence was accompanied by the following species, Codium arabicum of green algae, Cystoseira amentacea of brown algae, and Galaxaura rogusa, Jania rubens and Corallina elongate of red algae in Lattakia and Jableh beaches, while Caulerpa racemosa accompanied it in Tartus beach. This species spread in the shallow rocky bottom inshore layer in our study sites in great abundance compared to its abundance at the beginning of its spread, causing the deterioration of some other plant species Halophila stipulacea (Forsska˚l) Ascherson